Availability of aldo-keto reductase 1C3 and ATP-binding cassette B1 as therapeutic targets for alleviating paclitaxel resistance in breast cancer MCF7 cells. (22nd November 2022) - Matsunaga, Toshiyuki; Horinouchi, Misato; Saito, Haruhi; Hisamatsu, Aki; Iguchi, Kazuhiro; Yoshino, Yuta; Endo, Satoshi; Ikari, Akira
Abstract: Paclitaxel (PTX) is frequently utilized for the chemotherapy of breast cancer, but its continuous treatment provokes hyposensitivity. Here, we established a PTX-resistant variant of human breast cancer MCF7 cells and found that acquiring the chemoresistance elicits a remarkable up-regulation of aldo-keto reductase (AKR) 1C3. MCF7 cell sensitivity to PTX toxicity was increased by pretreatment with AKR1C3 inhibitor and knockdown of this enzyme, and decreased by its overexpression, inferring a crucial role of AKR1C3 in the development of PTX resistance. The PTX-resistant cells were much less sensitive to 4-hydroxy-2-nonenal and acrolein, cytotoxic reactive aldehydes derived from ROS-mediated lipid peroxidation, compared with the parental cells. Additionally, the resistant cells lowered levels of 4-hydroxy-2-nonenal formed during PTX treatment, which was mitigated by pretreating with AKR1C3 inhibitor, suggesting that AKR1C3 procures the chemoresistance through facilitating the metabolism of the cytotoxic aldehyde. The gain of PTX resistance additively promoted the aberrant expression of an ATP-binding cassette (ABC) transporter ABCB1 among the ABC transporter isoforms. The combined treatment with AKR1C3 and ABCB1 inhibitors overcame the PTX resistance and cross-resistance to another taxane-based drug docetaxel. Collectively, combined treatment with AKR1C3 and ABCB1 inhibitors may exert an overcoming effect of PTX resistance in breast cancer. Graphical Abstract: